Perceived clinician stigma and its impact on eating disorder treatment experiences: a systematic review of the lived experience literature - Gabriel Lubieniecki; Anne Nileshni Fernando; Alisha Randhawa; Sean Cowlishaw; Gemma Sharp (Journal of Eating Disorders)
Abstract Objective This systematic review examines the literature regarding perceived clinician stigma and treatment experiences of adult patients with eating disorders, emphasising lived experience perspectives. Method A systematic search was conducted across MEDLINE, EMBASE, PsycINFO, and the Cochrane Central Register of Controlled Trials [CENTRAL] to identify studies published from 1 January 2000 until 24 March 2024 that explored patient experiences of clinician attitudes and behaviours in eating disorder treatment. Eligible studies included those reporting on perceived clinician stigma and impacts on treatment outcomes. Results There were 11 studies that met the eligibility criteria. The studies encompassed various diagnoses, locations, and healthcare settings, reflecting a broad spectrum of experiences and contexts within treatment of eating disorders. Four key themes emerged across the studies: treatment engagement, where perceived clinician stigma led to reduced patient involvement; therapeutic alliances, with stigma compromising relationships between patients and healthcare providers; barriers to treatment and care, where stigma heightened obstacles to accessing support; and weight stigma. Discussion Despite the overall scarcity of evidence, these qualitative studies provide evidence of impacts of perceived clinician stigma on patient experiences in eating disorder treatment. These findings provide an initial understanding of negative effects of clinician attitudes such as dismissiveness and invalidation, which may hinder treatment adherence and therapeutic outcomes. Beyond addressing stigma, future research should explore how clinician behaviours can foster positive treatment experiences, such as patients feeling heard, respected, and understood. Clinicians’ reflective practices should focus on improving therapeutic alliances and fostering more inclusive, patient-centred care. Future studies should prioritise mixed-methods approaches to investigate how clinician stigma and positive care experiences influence treatment engagement, recovery trajectories, and long-term outcomes.